(untitled) (Scientific journal of the Fergana State University, 2024)
In the article, the theoretical and methodological foundations of the formation of ideals of military heroism in the thinking of young people, the socio-philosophical foundations of the formation of ideals of military heroism in the thinking of young people are studied. Also, philosophical factors of forming a sense of national pride in young people based on the ideals of military heroism are analyzed.